+0  
 
0
210
4
avatar

3x+(-4)=2x+9

Guest May 23, 2017
 #1
avatar+7266 
0

To solve this for x.....

3x + (-4) = 2x + 9

3x - 4 = 2x + 9

 

Add 4 to both sides of the equation.

3x = 2x + 9 + 4

3x = 2x + 13

 

Subtract 2x from both sides of the equation.

3x - 2x = 13

x = 13

hectictar  May 23, 2017
 #2
avatar
0

12=6/7x

Guest May 23, 2017
 #3
avatar+7266 
0

12 = \(\frac67\)x

 

Multiply both sides of the equation by \( \frac76 \)

 

12 * \( \frac76 \) = \(\frac67 \)x * \( \frac76 \)

 

14 = x

hectictar  May 23, 2017
 #4
avatar+80 
0

The answer is x=13

mathguardian23  May 23, 2017

17 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.